PENGARUH WAKTU TERHADAP KEKUATAN LASER TREE LT-40W-AA PADA RANCANG BANGUN MESIN CNC 3 AXIS BERBASIS ARDUINO UNO - Rusydi, Banu; Listiana, Reni (Jurnal Mahasiswa Terapan; Vol 1 No 3 (2025): Jurnal Mahasiswa Terapan, 2025)
This research aims to evaluate the effect of time on laser power on an Arduino Uno-based 3-axis CNC machine using the LT-40W-AA laser tree. In the development of this CNC machine, laser power is an important factor in determining the quality and precision of cutting or engraving materials. This research was carried out by measuring changes in laser power during various operational durations and analyzing its impact on the work results of CNC machines. The research methodology involves testing various laser emission durations on test materials of the same size and thickness. The data obtained was analyzed to identify the relationship between laser emission time and the resulting power, as well as its impact on cutting quality. The results showed that the laser power underwent significant changes as the emission time increased, with the potential to increase or decrease cutting efficiency depending on the duration of use. These findings can be used to optimize laser settings and improve the performance of 3-axis CNC machines in practical applications.